The Relative Importance of Symmetric and Asymmetric Shocks: the Case of United Kingdom and Euro Area - Gert Peersman (Oesterreichische Nationalbank (OeNB), 2007)
In this paper, we show how a simple model with sign restrictions can be used to identify symmetric and asymmetric supply, demand and monetary policy shocks in a two-country structural VAR. The results can be used to deal with several issues that are important in the OCA-literature. Whilst the method can be applied to many countries, we provide evidence for the UK versus the Euro Area which are compared versus the US as a benchmark. An important role for symmetric shocks with the Euro Area in explaining UK output fluctuations is found. However, the relative importance of asymmetric shocks, being around 20 percent in the long-run, cannot be ignored. In contrast, the degree of business cycle synchronization seems to have been higher with the US. Moreover, the historical average reaction of the policy rate to symmetric aggregate demand shocks was stronger in the UK than the Euro Area. We also confirm existing evidence of the exchange rate being an important independent source of shocks in the economy.
Keywords: C32; E42; F31; F33; 330; optimal currency areas; symmetric and asymmetric shocks; vector autoregressions